Troponin T3 regulates nuclear localization of the calcium channel Cavβ1a subunit in skeletal muscle - Zhang, Tan (2015)
The voltage-gated calcium channel (Cav) β1a subunit (Cavβ1a) plays an important role in excitation-contraction coupling (ECC), a process in the myoplasm that leads to muscle-force generation. Recently, we discovered that the Cavβ1a subunit travels to the nucleus of skeletal muscle cells where it helps to regulate gene transcription. To determine how it travels to the nucleus, we performed a yeast two-hybrid screening of the mouse fast skeletal muscle cDNA library and identified an interaction with troponin T3 (TnT3), which we subsequently confirmed by co-immunoprecipitation and co-localization assays in mouse skeletal muscle in vivo and in cultured C2C12 muscle cells. Interacting domains were mapped to the leucine zipper domain in TnT3 COOH-terminus (160-244 aa) and Cavβ1a NH2-terminus (1-99 aa), respectively. The double fluorescence assay in C2C12 cells co-expressing TnT3/DsRed and Cavβ1a/YFP shows that TnT3 facilitates Cavβ1a nuclear recruitment, suggesting that the two proteins play a heretofore unknown role during early muscle differentiation in addition to their classical role in ECC regulation.